The Role of Radiography in Detecting Endodontic Treatment Failures - Mustainah, Sakiya; Barunawaty, Barunawaty (Jurnal Medali, 2024)
Endodontic treatment is part of the conservation of teeth, which is the treatment of the inside of the teeth which aims to maintain the teeth as long as possible in the oral cavity. As long as endodontic treatment is carried out, it cannot be separated from supporting care, namely radiological photos. In addition to clinical assessments, radiological assessments need to be carried out to see the condition around the teeth and at the root tips. In addition, radiological photos were taken when filling the root canals with gutta-percha. At the final evaluation of endodontic treatment, radiological photographs still need to be done to see the final result whether there is an error or not.Radiographs made at the next visit can evaluate the periapical state, detect the healing process of the lesion or identify new diseases that may arise.18 The success of new treatment will be seen several months after treatment. Given that failure often occurs without signs and symptoms, radiographs are very important for evaluating the periapex status.